ANALISIS SISTEM PENGAMAN UTAMA UNTUK MENGAMANKAN BUSBAR 150 kV TERHADAP GANGGUAN DI GIS PECATU - Made Niken Ayu Larasati Danianto; I Gede Dyana Arjana; Cok. Gede Indra Partha (Program Studi Teknik Elektro UNUD, 2022)
GIS (Gas Insulated Switchgear) is a system of connecting and disconnecting the power grid which is packaged in a non-ferrous tube, using gaseous sulfur hexaflouride (SF6) as the insulation medium. The 150 kV of GIS Pecatu is located in Pecatu Village, South Kuta, Badung Regency, Bali Province. This GIS was built to help supply 120 MW of energy because of the load in Badung area, especially Pecatu and Nusa Dua, is increasing. So, it is necessary to know the differential relay current settings when there is a fault of short circuit in GIS Pecatu to produce an effective, selective and reliable safety system. When there is a fault of 11.58 kA the relay will work immediately within 0 SI, this proves that the differential relay with Instantaneous characteristics will immediately command a trip when the fault current has surpass the set value. From the calculation results, the setting of the main safety relay has worked in appropriate with the SPLN standard No. 52-1 1984 for the 150 kV system.